2012
DOI: 10.1017/s1041610212000865
|View full text |Cite
|
Sign up to set email alerts
|

Older people dying with dementia: a nationwide study

Abstract: Several areas of end-of-life care provision could be improved. Early communication and exploration of wishes and appointment of proxy decision-makers are important components of an early palliative care approach which appears to be initiated too infrequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…31 A Belgian nationwide mortality study through the Sentinel general practitioner (GP) network retrospectively reported place of death for ≥65-year-olds with GP-confirmed dementia. 32 In this study, 71% of those with severe dementia died in a care home, as did 41% with mild dementia. Although these percentages are again higher than we found, these findings are in line with our findings that dying in a care home is more likely with increasing cognitive impairment (mild/ moderate: 28%, severe: 61%).…”
Section: Comparison With Existing Literaturementioning
confidence: 50%
See 1 more Smart Citation
“…31 A Belgian nationwide mortality study through the Sentinel general practitioner (GP) network retrospectively reported place of death for ≥65-year-olds with GP-confirmed dementia. 32 In this study, 71% of those with severe dementia died in a care home, as did 41% with mild dementia. Although these percentages are again higher than we found, these findings are in line with our findings that dying in a care home is more likely with increasing cognitive impairment (mild/ moderate: 28%, severe: 61%).…”
Section: Comparison With Existing Literaturementioning
confidence: 50%
“…The Belgian results do not include sufficient detail to compare whether they also found the contrasting situation for the sub-set of individuals with severe cognitive impairment living in the community whom we found were the most likely group of all to move. 32 Other Sentinel programme reports highlighted admissions to hospital as highest closest to death for all older people. 17,35 Our data suggested most transitions occurred soon before death, but we lack data to compare time frames in such detail.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Yet, uptake of ACP is known to be low among people with dementia [13,14] while prognosis is poor. Decision-making in an acute setting concerning diagnostic and therapeutic interventions (including living wills, instructions regarding antibiotic therapy, resuscitation, or admission to an intensive care unit) is less complicated within the context of a previous discussion on preferences and personal goals of terminal care and management.…”
Section: Discussionmentioning
confidence: 99%
“…One of the components of ACP is the discussion on whether to initiate or refrain from diagnostic or therapeutic interventions. Yet, uptake of ACP is increasing in the general elderly population and in patients with CVD and cancer, but is known to be low among people with dementia [13,14]. However, life expectancy in dementia is poor and decision-making in an acute setting concerning diagnostic and therapeutic interventions (including living wills, instructions regarding antibiotic therapy, resuscitation, or admission to an intensive care unit) is less complicated within the context of a previous discussion on preferences and personal goals of terminal care and management.…”
Section: Introductionmentioning
confidence: 99%
“…However, a cross-national retrospective study showed that, in a population of patients who died non-suddenly, GP-patient discussion of treatment preferences occurred for 25% of patients in Belgium [9]. Cancer patients are also more often involved in the process of ACP than non-cancer patients, suggesting that initiation of ACP with other patient groups has its own challenges [10].…”
Section: Introductionmentioning
confidence: 99%